2018
DOI: 10.1016/j.retrec.2018.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of network level benefits of reliability improvements in intermodal freight transport

Abstract: An important problem in the assessment of reliability benefits of transport projects is that link level improvements must be translated to network level, so that they can be economically valued based on users' trips from origins to destinations. For intermodal transport, shipments follow a chain with more than one mode. Generally, this requires aggregation of travel time distributions that are not additive. We propose an approach that estimates the change in transport time reliability of an intermodal transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…As reviewed before, this study considers the transportation reliability with stochastic travel time and the stochastic operation time at nodes. It is difficult to quantify the reliability of intermodal transportation under multiple parameter uncertainties, and related studies generally use simulation methods [37] or estimate the overall distribution [38] to quantity.…”
Section: Constructing the Objectives Of The Optimization Modelmentioning
confidence: 99%
“…As reviewed before, this study considers the transportation reliability with stochastic travel time and the stochastic operation time at nodes. It is difficult to quantify the reliability of intermodal transportation under multiple parameter uncertainties, and related studies generally use simulation methods [37] or estimate the overall distribution [38] to quantity.…”
Section: Constructing the Objectives Of The Optimization Modelmentioning
confidence: 99%
“…According to decision models, the optimal mode of transshipment distribution was obtained based on a set of parameters that ensure the same spatial displacement, fewer expenditures, reduction in the transportation time of goods in transit, and warranty of cargo safety. Zhang et al [2] demonstrated a solution in a cost-benefit analysis context with user valuations of intermodal freight transport reliabilities. The authors proved as well that projects for the renovation and expansion of a transshipment terminal were found to be more effective compared to a project that improves the rail haulage speed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A transshipment terminal is the intermediate node added to an intermodal transport network when combining/linking two or more liner services [1]. Transshipment terminals play a significant role in efficient freight delivery as an important link of intermodal transport chains, as has been mentioned by Zhang et al [2] and other researchers. As a part of transport and logistics systems, the terminals provide material handling and allow for transshipment between various transport modes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the decisive factor is speed, the best solution will be air or road transport. However, if the main criterion is reliability or low cost, rail transport is an option worth consideration (Zhang et al, 2018;2019). A transport service provider offering transport services for the benefit of a company impacts the performance of the supply chain items it owns (Zitrický et al, 2017).…”
Section: Introductionmentioning
confidence: 99%